2021
DOI: 10.1021/acs.chemmater.1c00448
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Structural and Energetic Disorder in High-Mobility Polymer Semiconductors via Doping with Nitroaromatics

Abstract: Molecular doping has emerged as a powerful strategy to tune the charge transport properties of organic field-effect transistors (OFETs). However, the limited tool-box of molecular dopants and unresolved challenges of stability, uniformity of the doping, and matching the energy levels constrain the achieved OFET device performance and thwart the practical applications. Here, nitrofluorene (NF) acceptors are introduced as effective p-dopants in polymer OFETs, resulting in outstanding device performance of a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…DPP-based dual-acceptor polymers have several advantages in this aspect: (i) The two acceptors increase the electron affinity to facilitate electron transport properties. Combined with commonly used electron-donating flanking groups of DPP, it is easier to achieve ambipolar properties in OFETs; (ii) the flanking group variation of DPP is a simple yet effective strategy to fine-tune the charge carrier polarity as reported in our previous publication; (iii) the doping/additive strategy makes positive influences on the OFET device performance with DPP-based semiconductors. , In terms of these favorable features and considering the lack of studies on the carrier polarity tunability of ambipolar transistors through the additive strategy, we developed two new DPP-based dual-acceptor polymers by selecting BTI as another acceptor unit. By varying the flanking groups of DPP and through the additive strategy, the charge carrier polarity tunabilities of both ambipolar polymers in OFETs are studied in detail.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…DPP-based dual-acceptor polymers have several advantages in this aspect: (i) The two acceptors increase the electron affinity to facilitate electron transport properties. Combined with commonly used electron-donating flanking groups of DPP, it is easier to achieve ambipolar properties in OFETs; (ii) the flanking group variation of DPP is a simple yet effective strategy to fine-tune the charge carrier polarity as reported in our previous publication; (iii) the doping/additive strategy makes positive influences on the OFET device performance with DPP-based semiconductors. , In terms of these favorable features and considering the lack of studies on the carrier polarity tunability of ambipolar transistors through the additive strategy, we developed two new DPP-based dual-acceptor polymers by selecting BTI as another acceptor unit. By varying the flanking groups of DPP and through the additive strategy, the charge carrier polarity tunabilities of both ambipolar polymers in OFETs are studied in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Second, DPP-based polymers tend to have ambipolar transport properties because the flanking groups are generally electron-donating or weak electron-accepting units. ,, Ambipolar semiconductors are more suitable candidates for the study of charge carrier polarity tunability because they allow both holes and electrons flowing in the conducting channel of OFETs under negative and positive gate voltage, respectively. Third, the ease of synthesis and high device performance make DPP-based polymers the model materials in OFET device engineering, for example, chemical doping/additive. Luo et al reported that the addition of ionic NMe 4 I to the DPP and thienothiophene polymer can remarkably improve the hole mobility to 26.2 cm 2 V –1 s –1 . A series of characterizations indicate that the improvement is not caused by chemical doping but ascribed to the backbone coplanarity improvement for more favorable molecular packing and stronger π–π interactions .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations